Gendered Verbal Aggressiveness on the Instagram Account @Gitasav: An Ethical Analysis from the Perspective of Ibn Miskawayh - Rizka Sania; T. Faizin; Mannan, Mannan (Faculty of Ushuluddin and Philosophy, 2024)
This article explores gender-based verbal aggressiveness on the Instagram account @gitasav through the lens of Ibn Miskawayh’s ethical framework. It addresses two central questions: What is the nature of verbal aggressiveness on Gita Savitri’s Instagram account, and how can this gender-laden verbal aggressiveness be examined through Ibn Miskawayh’s Islamic ethical perspective? The study adopts a qualitative approach, employing netnography as a method to gather data by downloading and preserving posts and digital traces. Netnography allows the researcher to observe social phenomena within the digital realm. The findings indicate that Ibn Miskawayh’s ethics strongly discourage gender-based verbal aggression. While Ibn Miskawayh does not explicitly discuss aggression in his ethical discourse, his concepts of goodness, happiness, and virtue offer a framework for ethical conduct. This article posits that individuals should strive to maintain a balanced and flexible demeanor across various contexts, as moral virtue is often found in the middle ground between two extremes.